If it's not what You are looking for type in the equation solver your own equation and let us solve it.
22=2(2x-4)+2
We move all terms to the left:
22-(2(2x-4)+2)=0
We calculate terms in parentheses: -(2(2x-4)+2), so:We get rid of parentheses
2(2x-4)+2
We multiply parentheses
4x-8+2
We add all the numbers together, and all the variables
4x-6
Back to the equation:
-(4x-6)
-4x+6+22=0
We add all the numbers together, and all the variables
-4x+28=0
We move all terms containing x to the left, all other terms to the right
-4x=-28
x=-28/-4
x=+7
| 5x−12=23 | | 6x-16=3x+9 | | 3x-1=-5x+63 | | 2p+39=3 | | -10(s+2)=-47 | | 9(u+2)=27 | | 3÷4d+1÷5d+5d=d | | 3(q-4)=24 | | 3÷4+1÷5+5=d | | 2(e+5)=20 | | 78-2x=6 | | 0.25^x=16 | | y/3+1=6/y | | 3(x+2=11 | | 2h-2=16 | | 2(3x-1)=5x-5 | | 3^x+3-3^x+1=24 | | x(x+3)+5(x+3)=x+3x+5x+15 | | 2x+3*2^(x+1)=28 | | 2x+3*2^x+1=28 | | 7-2xx=-3 | | 5m-1=9 | | -10(s+5)=-72 | | –6+x=–3 | | _m-÷3=4 | | -6(3w-3)+2w=2(w+8) | | 2-x=9+2x | | -4(4x-2)+4x=9+3(2x-3) | | 3(2x+4)+2=-5x+25 | | 12-1,28(x-5)=22-2(x+4) | | 1+x/2-1/2-x/4+1/4=x/3+3/3 | | 3t+4=t13 |